ANALISIS PROBLEMATIKA PENDIDIKAN INKLUSI DALAM PELAKSANAANNYA DI INDONESIA - siti nurhana; Syahdan alqowi; Vamelia putri hospita; Opi andriani (JOURNAL SAINS STUDENT RESEARCH, 2024)
The launch of inclusive education in Indonesia with the aim of facilitating the educational needs of children with special needs (ABK) has been widely implemented throughout Indonesia, especially in big cities, but in its implementation there have been many obstacles or problems in schools, especially for teachers. This research aims to determine the problems experienced by teachers and schools in implementing inclusive education at the elementary school level in the Muara Bungo City area. The research subjects were teachers who taught at schools providing Inclusive Education. Data was obtained through an open-ended questionnaire (open questions). Research shows that there are various problems encountered by teachers related to school readiness itself, such as a lack of teacher competence in dealing with ABK students, problems related to the lack of parental concern for ABK. Solutions for implementing learning in the classroom, teachers must implement modifications to the classroom learning process.